EFFECTIVENESS OF â€œAMDALâ€ IMPLEMENTATION IN PROTECTING ENVIRONMENTAL DAMAGE DUE TO INDUSTRIAL - Novenna Tarigan, Dea Grace (Communale Journal, 2023)
To prevent environmental damage due to industrial activities in Indonesia, AMDAL is an essential document to prepare. AMDAL has an instrument that aims to prevent environmental damage and prevent environmental damage (Law No.32 of 2009). In making and implementing AMDAL, we must pay attention to ecological sustainability so that we do not cause significant impacts that are harmful to current and future generations. This research aims to find and collect information coherently and comprehensively regarding the effectiveness of AMDAL implementation in preventing environmental damage due to industrial activities in Indonesia. This research uses a literature study method on activities that are organized systematically and scientifically using an interdisciplinary and even multidisciplinary approach to answer the effectiveness of AMDAL implementation in preventing environmental damage due to industrial activities in Indonesia. The results of this study indicate that the effective implementation of AMDAL activities is significant and must be implemented by all businesses, companies, and industries. AMDAL is one of the requirements in environmental permits to prevent ecological damage and pollution around the activities of these companies, businesses, and industries.